Dampak Pengaruh Gadget Terhadap Perkembangan Bahasa Anak Usia Dini di RA Dewi Sartika II Pakal Keacamatan Pakal Kota Surabaya - Nurkhikmah, Fitri; Sidiq, Adelia Miranti; Umairi, Mushab Al (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2024)
In this modern era, everyone from toddlers to adults are very familiar with gadgets and use them. Even toddlers are more adept at using gadgets than adults. Therefore, there are many impacts and influences of the gadget itself, ranging from positive and negative. The negative impact of using gadgets for young children is the delay in their language development. This research aims: (1) To understand the level of language development of group A early childhood children in RA Dewi Sartika II Pakal Village, Pakal District, Surabaya City. (2) Understand the flashcard game activities in group A at RA Dewi Sartika II to find out how far their language has developed. This research is qualitative descriptive research. This research is intended to understand the phenomena experienced by the research subjects. The data collection techniques used in this research are observation, interviews and documentation. The research results show that language development in early childhood is important as a basic foundation for learning and can influence social emotional development and cognitive development. Through the media of letter games or flashcards the enthusiasm and enthusiasm of students can be seen. Letter game activities carried out gradually and continuously will teach young children the concept of developing language in a fun way.